2020
DOI: 10.3389/fmed.2020.00489
|View full text |Cite
|
Sign up to set email alerts
|

Care Professionals Manage the Future, Frail Older Persons the Past. Explaining Why Frailty Management in Primary Care Doesn't Always Work

Abstract: Frailty management focuses on optimizing the physical and psychological functioning of older people with frail health through early risk identification and intervention in primary care. Such care programs demand a joint effort by primary care professionals and older persons, one in which professionals are expected to promote or facilitate self-management practices and older persons are expected to adhere to the professional advice. It is known that patients and professionals hold different perspectives on frai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Whereas medicine in general and Emergency Medicine in particular is disease-oriented and highly protocolized, older people in the Emergency Department (ED) often present with frailty syndromes or atypical complaints that may make protocol-driven approaches unsuitable. Although knowledge on frailty syndromes is increasing, it remains a challenge to translate this knowledge reliably into daily clinical care [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas medicine in general and Emergency Medicine in particular is disease-oriented and highly protocolized, older people in the Emergency Department (ED) often present with frailty syndromes or atypical complaints that may make protocol-driven approaches unsuitable. Although knowledge on frailty syndromes is increasing, it remains a challenge to translate this knowledge reliably into daily clinical care [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore unsurprising that the approach to management was similarly non-uniform and largely dependent on clinician’s role and experience. This finding was similarly replicated in a focus group study of community nurses in Scotland [ 28 ], and of a study of nine patients and their health professionals in the Netherlands [ 29 ]. There is a strong argument for addressing the identification of frailty to facilitate a more cohesive and structured approach.…”
Section: Discussionmentioning
confidence: 59%
“…A holistic approach to assessment has also been reported by UK community nurses, general practitioners, and other HCPs in qualitative interview and focus group studies ( Coker et al, 2019 ; Mulla et al, 2021 ; Papadopoulou et al, 2021 ) and European surveys ( Bruyère et al, 2017 ). Qualitative studies in the Netherlands have found that proactive monitoring, planning, multidisciplinary collaboration are key parts of primary care frailty management ( La Grouw et al, 2020 ), with nurses feeling that optimizing nutritional status, support from the environment and improving mobility were especially important ( Gobbens et al, 2022 ). The clear changes in care as a result of frailty assessment are encouraging, as qualitative work suggests that making a difference and not being a tick box exercise is important to motivate HCPs to identify frailty ( Anantapong & Tinker, 2019 ; Mulla et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clear changes in care as a result of frailty assessment are encouraging, as qualitative work suggests that making a difference and not being a tick box exercise is important to motivate HCPs to identify frailty ( Anantapong & Tinker, 2019 ; Mulla et al, 2021 ). However, it should be acknowledged that patients and HCPs often have differing perspectives on frailty management and what can be achieved ( D’Avanzo et al, 2017 ; La Grouw et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation